The Challenges of ICT Utilization for Effective and Efficient Administration in Private and Public Institutions - publisher, publisher; Ukwuije , Chima B. (African Journal of Education,Science and Technology (AJEST), 2017)
Information and communication technology, currently and popularly known by the acronym ICT is now globally embraced. The speed at which ICT is developing is tremendous. As such, it has manifested virtually in all aspect of human existence as a tool to reduce work load, make administrative decisions more accurate, realizable and development oriented and even make life easier for the common man. The speed at which technology is developing is tremendous to the extent that even children of 6 years and above have been given a place in the world of technology. As such, no singular effort no matter how we try to explain it, can capture in a holistic sense the relevance of ICT in the modern day administrative process. This is why corporate bodies and non corporate entities are making more pronounced effort to acquaint their personnel with the development trends in the world of technology. leaning on this backdrop, this paper therefore tried to identify what constitute ICT, areas where it is proved to be most relevant, the challenges arising there-from and made recommendations on how to remedy the challenges arising from the use of modern day ICT. The Study used the secondary source as its main source of data collection. Books, articles from journals, newspapers and many other printed works were consulted.